Sulfate Transport in Penicillium chrysogenum: Cloning and Characterization of the sutA and sutB Genes - van de Kamp, Mart (American Society for Microbiology, 1999)
In industrial fermentations, Penicillium chrysogenum uses sulfate as the source of sulfur for the biosynthesis of penicillin. By a PCR-based approach, two genes, sutA and sutB, whose encoded products belong to the SulP superfamily of sulfate permeases were isolated. Transformation of a sulfate uptake-negative sB3 mutant of Aspergillus nidulans with the sutB gene completely restored sulfate uptake activity. The sutA gene did not complement the A. nidulans sB3 mutation, even when expressed under control of the sutB promoter. Expression of both sutA and sutB in P. chrysogenum is induced by growth under sulfur starvation conditions. However, sutA is expressed to a much lower level than is sutB. Disruption of sutB resulted in a loss of sulfate uptake ability. Overall, the results show that SutB is the major sulfate permease involved in sulfate uptake by P. chrysogenum.